Clinical utility and cost‐effectiveness analysis of chromosome testing concomitant with chromosomal microarray of patients with constitutional disorders in a U.S. academic medical center. Issue 2 (16th August 2021) - Su, Meng; Page, Stephanie; Haag, Mary; Swisshelm, Karen; Hennerich, Deborrah; Graw, Sharon; LeRoux, Jamie; Brzeskiewicz, Peter; Svihovec, Shayna; Bao, Liming
Abstract: Chromosomal microarray (CMA) is now widely used as first‐tier testing for the detection of copy number variants (CNVs) and absence of heterozygosity (AOH) in patients with multiple congenital anomalies (MCA), autism spectrum disorder (ASD), developmental delay (DD), and/or intellectual disability (ID). Chromosome analysis is commonly used to complement CMA in the detection of balanced genomic aberrations. However, the cost‐effectiveness and the impact on clinical management of chromosome analysis concomitant with CMA were not well studied, and there is no consensus on how to best utilize these two tests. To assess the clinical utility and cost‐effectiveness of chromosome analysis concomitant with CMA in patients with MCA, ASD, DD, and/or ID, we retrospectively analyzed 3, 360 postnatal cases for which CMA and concomitant chromosome analysis were performed in the Colorado Genetic Laboratory (CGL) at the University Of Colorado School Of Medicine. Chromosome analysis alone yielded a genetic diagnosis in two patients (0.06%) and contributed additional information to CMA results in 199 (5.92%) cases. The impact of abnormal chromosome results on patient management was primarily related to counseling for reproductive and recurrence risks assessment (101 cases, 3.01%) while a few (5 cases, 0.15%) led to changes in laboratory testing and specialist referral (25 cases, 0.74%). The incremental cost‐effectiveness ratio (ICER) of combined testing demonstrated the cost of each informative chromosome finding was significantly higher for patients with clinically insignificant (CI) CMA findings versus clinically significant (CS) CMA results. Our results suggest that a stepwise approach with CMA testing with reflex to chromosome analysis on cases with CS CMA findings is a more cost‐effective testing algorithm for patients with MCA, ASD, and/or DD/ID.